2010
DOI: 10.1037/a0019140
|View full text |Cite
|
Sign up to set email alerts
|

The role of familism in the relation between parent–child discord and psychological distress among emerging adults of Mexican descent.

Abstract: Although parent-child discord is a predictor of distress among emerging adults, little is known about this important link among Mexican-descent populations. This is an important gap, given Mexican Americans' high risk for psychological distress and their expected high value placed on close family ties. This topic was studied in a sample of 392 college students from El Paso, TX (n = 193) and from Ciudad Juárez, México (n = 199). The authors tested a stress-appraisal model with self-report measures of familism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…These difficult scenarios may be especially distressing to someone high in familism, because they violate positive expectations for family relationships or overwhelm an individual’s ability to meet their family obligations. Under circumstances characterized by conflict or other types of distress, familism may well heighten the risk of poorer mental health (e.g., Hernández, Ramírez García, & Flynn, 2010; Zayas & Pilat, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…These difficult scenarios may be especially distressing to someone high in familism, because they violate positive expectations for family relationships or overwhelm an individual’s ability to meet their family obligations. Under circumstances characterized by conflict or other types of distress, familism may well heighten the risk of poorer mental health (e.g., Hernández, Ramírez García, & Flynn, 2010; Zayas & Pilat, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally 'familism' , a cultural value characteristic that is defined as "the subordination of individual interests to those of the family" [40], has also been linked to ethnic minorities [41]. Studies have shown that expectations of family harmony or 'familism' may create increased distress when conflicts within the family arise [5]. Cultural factors may also affect perceptions of a 'normally' functioning family, 'harsh' parenting and child behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Family functioning and parenting factors have been found to vary between ethnic minority and majority groups, with ethnic minorities showing a greater risk of, amongst others, poor family functioning [5], parenting stress [6] and harsh parenting [7,8]. These differences can partly be explained by socioeconomic status [9].…”
Section: Introductionmentioning
confidence: 99%
“…Latino family research and related cultural theory emphasize interpersonal relationships within the extended family as uniquely relevant to psychosocial distress and depression for Latinos due to strong expectations that the family is the primary resource for coping during times of stress (Diaz et al 2007). Thus, high levels of family stress may be especially threatening for women of Mexican heritage because it violates cultural expectations about family relationships (Hernández et al 2010), particularly during pregnancy, when the traditional role of the family is to support the expectant mother and reduce her exposure to stressful experiences that might compromise her health and her baby (Kruckman 1992; Niska et al 1998). …”
Section: Introductionmentioning
confidence: 99%